2021
DOI: 10.3390/chemosensors9090246
|View full text |Cite
|
Sign up to set email alerts
|

Chemiresistors Based on Li-Doped CuO–TiO2 Films

Abstract: Chemiresistors based on thin films of the Li-doped CuO–TiO2 heterojunctions were synthesized by a 2-step method: (i) repeated ion beam sputtering of the building elements (on the Si substrates and multisensor platforms); and (ii) thermal annealing in flowing air. The structure and composition of the films were analyzed by several methods: Rutherford Backscattering (RBS), Neutron Depth Profiling (NDP), Secondary Ion Mass Spectrometry (SIMS), and Atomic Force Microscopy (AFM), and their sensitivity to gaseous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The battery industry relies on lithium for its high energy density and storage capacity. This is why scientists have been interested in mixing lithium with numerous metal oxides such as CuO [9] and SnO 2 [10], as these materials play an effective role in battery applications and energy storage. Studies have shown that lithium has a significant effect on the electrical and optical properties of metal oxides [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The battery industry relies on lithium for its high energy density and storage capacity. This is why scientists have been interested in mixing lithium with numerous metal oxides such as CuO [9] and SnO 2 [10], as these materials play an effective role in battery applications and energy storage. Studies have shown that lithium has a significant effect on the electrical and optical properties of metal oxides [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lupan et al [32] obtained an enhanced gas response to ethanol compared to hydrogen in the temperature range between 523 and 623 K, which was opposite the result of Barreca et al [40], who showed that the response to hydrogen is about two times higher than that of ethanol. Furthermore, a mixed oxide of 50% TiO 2 and 50% CuO was found to be more sensitive to NO 2 than to H 2 , and could be further improved by adding Li to the mixture [41,42].…”
Section: Introductionmentioning
confidence: 99%